PENGARUH PENYULUHAN KESEHATAN TERHADAP PENGETAHUAN IBU TENTANG STIMULASI PERKEMBANGAN BALITA USIA 3-5 TAHUN DI POSYANDU SAKURA KELURAHAN GUNUNG MAS TELUK BETUNG SELATAN, LAMPUNG TAHUN 2016 - Endang Sri Wahyuni; Siti Indarti (Program Studi Ilmu Keperawata Fakultas Ilmu Kesehatan Universitas Malahayati, 2019)
ABSTRACT: DIETARY SODIUM INTAKE: KNOWLEDGE AND INTERDIALYTIC WEIGHT GAIN IN HEMODIALYSIS PATIENTS IN LAMPUNG PROVINCE- INDONESIABackground: A total of 44% of deaths in patients CKD on HD are caused by cardiovascular disease that related to uncontrolled interdialytic weight gain (IDWG). The IDWG increase is due to excessive sodium and fluid intake. This study aims to determine the relationship between characteristics and level of knowledge about fluid intake and sodium with IDWG .Methods:This study was a cross sectional study with a total sample of 74 people with CKD on HD twice a week in RSUD Dr H Abdul Moeloek Lampung in 2018 who were determined by purposive sampling. Results:The majority of respondents were male (63.5%) with educational background were elementary / junior high school (33.8%), jobs were laborers (25.7%) and 70,27% ever get nutritional counseling. The average increase in IDWG weight is 2.0015 ± 1.2537 kg with an average percentage of IDWG of 3.569 ± 2.34%. The result of statistic test showed no significant correlation between sex (p = 0.099), age (p = 0.709), education (p = 0.565), counseling status (p = 0.649), level of knowledge about sodium intake (p = 0.109) and fluid intake (p = 0.799) with IDWG. More intensive education and motivation by dietitian are needed in order to increase the knowledge of CKD on HD patient about food / drink that high in sodium and fluids also how to control thirst, sodium and fluid intake.Keywords: Characteristics, knowledge of fluid intake, knowledge of natrium intake, interdialytic weight gainPENDAHULUAN: Sebanyak 44% kematian pada pasien GGK on hemodialisis disebabkan oleh penyakit kardiovaskuler yang berhubungan dengan interdialytic weight gain (IDWG) yang tidak terkontrol. Kenaikan IDWG sebagai akibat asupan natrium dan cairan yang berlebihan. Penelitian ini bertujuan untuk mengetahui hubungan antara karakteristik, tingkat pengetahuan tentang asupan cairan dan natrium dengan IDWG.METODE: Penelitian ini menggunakan rancangan cross sectional dengan sampel berjumlah 74 orang penderita GGK yang menjalani HD 2 kali seminggu di RSUD Dr H Abdul Moeloek Lampung tahun 2018 yang ditentukan secara purposive sampling.HASIL:Responden terbanyak adalah laki-laki (63,5%, pendidikan SD/SMP (33,8%), pekerjaan buruh (25,7%) dan pernah mendapat konseling gizi (70,27%). Rata-rata IDWG sebesar 2,0015 ± 1,2537 kg dengan IDWG rata-rata 3,569 ± 2,341%. Hasil uji Chi Square menunjukkan tidak ada hubungan yang bermakna antara jenis kelamin (p=0,099), usia (p=0,709), pendidikan (p=0,565), status konseling (p=0,649), tingkat pengetahuan tentang asupan natrium (p=0,109) dan asupan cairan (p=0,799) dengan (IDWG). Edukasi dan motivasi yang lebih intensif oleh ahli gizi diperlukan dalam rangka meningkatkan pengetahuan pasien GGK on HD tentang bahan makanan/minuman tinggi natrium dan cairan serta cara mengendalikan asupan natrium, cairan dan rasa haus.